Analysis of Factors Causing Misconceptions in Plane Geometry among Fifth Grade Elementary School Students - Rachmat Imam Muslim; Meilan Tri Wuryani; Utomo Utomo; Muiz Ghifari (Universitas Negeri Malang, 2025)
Abstract: Misconceptions are often the cause of low student mathematics learning outcomes. In this study the authors seek to uncover the factors that cause students' misconceptions about plane shapes. This study uses a qualitative method with a case study approach. This research is based on the problem that there are still many students who are wrong in answering several questions in the form of stories. In this study two students were taken using a purposive sampling technique as research subjects. From the research results, it was found that the cause of students' misconceptions in answering non-routine questions was the low understanding of students' definitions. The low understanding of definitions occurs because learning only relies on one teaching material in which the teaching material has very little information. In addition, the lack of use of teaching media by teachers results in students not being able to recognize other forms of flat shapes according to the definition. Apart from that, the lack of examples of flat shapes given makes students' understanding of definitions shallow. When given a flat shape with a different shape, students experience confusion. Abstrak: Miskonsepsi sering menjadi penyebab rendahnya hasil belajar matematika siswa. Dalam penelitian ini penulis berusaha mengungkap faktor-faktor penyebab miskonsepsi siswa tentang bangun datar. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Penelitian ini didasari oleh permasalahan bahwa masih banyak siswa yang salah dalam menjawab beberapa soal berbentuk cerita. Dalam penelitian ini diambil dua orang siswa dengan menggunakan teknik purposive sampling sebagai subjek penelitian. Dari hasil penelitian ditemukan bahwa penyebab miskonsepsi siswa dalam menjawab soal nonrutin adalah rendahnya pemahaman siswa terhadap definisi. Rendahnya pemahaman definisi terjadi karena pembelajaran hanya bertumpu pada satu bahan ajar yang mana bahan ajar tersebut informasinya sangat sedikit. Selain itu, minimnya penggunaan media ajar oleh guru mengakibatkan siswa tidak mampu mengenali bentuk bangun datar lainnya sesuai definisi. Selain itu, minimnya contoh bangun datar yang diberikan membuat pemahaman siswa terhadap definisi menjadi dangkal. Ketika diberikan bangun datar dengan bentuk yang berbeda, siswa mengalami kebingungan.